Effects of Whole-Body Vibration Therapy on Quadriceps Function in Patients With Anterior Cruciate Ligament Reconstruction: A Systematic Review. (March 2022) - Qiu, Jihong; Ong, Michael Tim-Yun; Leong, Hio Teng; He, Xin; Fu, Sai-Chuen; Yung, Patrick Shu-Hang
Context: Quadriceps dysfunction is common for patients after anterior cruciate ligament reconstruction (ACLR). Whole-body vibration (WBV) could effectively treat quadriceps dysfunction. Objective: To summarize WBV protocols for patients with ACLR and to evaluate the effects of WBV on quadriceps function. Data Sources: PubMed, CINAHL, SportDiscus, Web of Science, Medline, and Embase were searched from inception to January 2020. Study Selection: Randomized controlled trials recruiting patients with ACLR, using WBV as intervention, and reporting at least 1 of the following outcomes, strength, rate of torque development (RTD), and voluntary activation ratio of quadriceps, were included. Study Design: Systematic review. Evidence Level: Level 3. Methods: This systematic review was reported according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Quality of evidence was determined by PEDro criteria and GRADE system. Participant characteristics, interventions, and the relevant results of the included studies were extracted and synthesized in a narrative way. Results: In total, 8 studies were included. Of these, 2 studies had serious risk of bias. Five of 8 studies implemented a series of WBV program ranging from 2 to 10 weeks in duration, while the other 3 studies implemented a single session of WBV. Eight WBV protocols were reported. The reported outcomes consisted of quadriceps strength, RTD, and central activation ratio. WBV protocols were heterogeneous. Low quality of evidence supported that exclusive conventional rehabilitation was more effective than exclusive WBV therapy in increasing quadriceps strength. Low quality of evidence supported that WBV combined with conventional rehabilitation was more beneficial in increasing quadriceps strength when compared with conventional rehabilitation alone. Very low quality of evidence supported the efficacy of a single session of WBV on quadriceps function. Conclusions: There is no standardized WBV protocol for patients with ACLR, and the effectiveness of WBV in rehabilitation on quadriceps function remains inconclusive.